Možnost ponovne uporabe hmelja po hladnem hmeljenju - Kočevar Baloh, Ana (Hmeljarski bilten, 2025)
This study investigates the potential for reusing hops after the use in dry hopping process, during which low temperatures prevent the extend isomerization of alpha-acids. The aim was to evaluate whether such hops, once dried, retain sufficient quantity of bitter compounds for effective reuse in conventional kettle hopping. Two hop varieties, Styrian Dragon and Aurora, were used in three- and five-day dry hopping treatments, then dried and reused in kettle hopping. Bitterness was determined spectrophotometrically (IBU) and by high-performance liquid chromatography (HPLC). The results showed that alpha-acid content decreased by 29% in Aurora and by 36% in Styrian Dragon after dry hopping. Nevertheless, reused hops produced comparable or even higher concentrations of iso-alpha-acids than fresh hops, particularly after 60 minutes of wort boiling. The highest measured bitterness values exceeded 90 IBU, confirming that hops retain a sufficient bitterness potential after dry hopping. These findings demonstrate that reusing hops after dry hopping is technologically feasible and represents a sustainable approach to reducing waste and raw material costs in the brewing industry.
Keywords: bitterness; dry hopping; grenčica; hladno hmeljenje; hmelj; hops; iso-alpha-acids; izo-alfa-kisline; ponovna uporaba; reuse